2018
DOI: 10.1177/1464884918760673
|View full text |Cite
|
Sign up to set email alerts
|

Which bedrock in a sea of change?

Abstract: In answer to the question of how journalism studies can prove its continued significance, this article argues that journalism skills should be seen as bedrock for journalism studies. From a historical perspective, journalism studies has grown out of journalism education, with its emphasis on training journalists. From a global perspective, it is the skill of sourcing, verifying, and communicating news, which is common to journalists around the world, and sets them apart from other information providers. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This issue has long been debated in many quarters, as has the question of ‘Who is a journalist?’ ( Hanusch, 2020 ; Hanitzsch & Vos, 2018 ; Hermida, 2019 ; Zelizer, 2004 ; 2017 ). From the literature it is obvious that the 20th century focus on news and newsrooms still shapes a large body of Western academic scholarship ( Josephi, 2016 ; Wahl-Jørgensen, 2009 ) and some still hope that institutional journalism will continue to have impact (e.g. Reese, 2021 ), even if promises of autonomy ring hollower than ever.…”
Section: Researching Freelance Journalistsmentioning
confidence: 99%
“…This issue has long been debated in many quarters, as has the question of ‘Who is a journalist?’ ( Hanusch, 2020 ; Hanitzsch & Vos, 2018 ; Hermida, 2019 ; Zelizer, 2004 ; 2017 ). From the literature it is obvious that the 20th century focus on news and newsrooms still shapes a large body of Western academic scholarship ( Josephi, 2016 ; Wahl-Jørgensen, 2009 ) and some still hope that institutional journalism will continue to have impact (e.g. Reese, 2021 ), even if promises of autonomy ring hollower than ever.…”
Section: Researching Freelance Journalistsmentioning
confidence: 99%
“…These results are further supported by the comparative analysis of digital competence models. The analysis results have shown that there is a high proliferation of studies focused on competencies development related to improving organizational communication and marketing (e.g., Schaich, 2012), establishing networks for professional collaboration (e.g., Josephi, 2019), or making use of reflective practise (e.g., Aceituno et al, 2014;Jiang & Rafeeq, 2019;Macmillan, 2014). On the contrary, neglecting competencies development related to personalizing differentiated learning itineraries and achieving the active participation of professionals, fostering an active and creative commitment (e.g., Reilly, 2018;Robinson et al, 2021;Stoker, 2015).…”
Section: Discussionmentioning
confidence: 99%